Insights on routing and scheduling approaches in the IoT from the perspective of energy, QoS, and security–a systematic review - Rajeshwari Kenchammana Hosakote Nanjappa; Manuvinakurike Narasimha Sastry Suma (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
The internet of things (IoT) has been conceptualized to bring more efficient and seamless connectivity to a large number of low-power and low-cost embedded devices. In the context of IoT, limited radio resources create new challenges, such as collisions and access conflicts. Another challenge arises in dealing with energy constraints, as battery-powered IoT sensors have limited energy capacity in the sensing layer. Consequently, routing mechanisms play a fundamental role in dealing with route optimization and reliable data transmission problems in the transport layer, whereas broadcast and link scheduling are also considered as appealing solutions for fulfilling the energy efficiency, collision-free transmissions and latency requirements in the IoT. Also, security vulnerabilities are hard to identify in the IoT perception and transport layer due to its ad-hoc network topological factors. Thus, deploying efficient routing schemes in IoT demands effective collaborative solutions for cost-effective and secure route formation with energy-aware scheduling performance, which were not, explored much in the past. This investigation thereby analyses the strengths and limitations of existing efficient routing and scheduling solutions in IoT and extracts the critical findings which could provide quick survey to many researchers in this application area.